Vehicle telematics data for urban freight environmental impact analysis. (January 2022) - Hu, Simon; Shu, Siqi; Bishop, Justin; Na, Xiaoxiang; Stettler, Marc
Abstract: Road freight transport is one of the major contributors to greenhouse gas and air pollutant emissions. Hence, it is increasingly regulated in urban areas to reduce its impact on the environment and human health. The rich data available from telematics has the potential to provide high-resolution information, yet research has not been conducted to understand, evaluate, and ultimately improve the operation and impacts of urban road freight. This paper demonstrates the role of vehicle telematics data in enabling quantitative assessment of the impacts of urban freight transport for the effective management of relevant policies. We present a comprehensive data-driven approach that provides a robust quantitative evaluation and applies it to a case study of the London Lorry Control Scheme (LLCS) policy in UK. We show that, for the studied freight operator, the LLCS policy affects their drivers' route choice both inside and outside the restricted hours. The spatio-temporal distributions of different parameters including traffic speeds, fuel economy and emissions at different times of the day are compared and analyzed. The results indicate that the unintended consequences of urban freight transport policies can include an extra 15% vehicle-km traveled per trip and 12% liter of fuel consumed per trip.